Clinical and histopathological profile of basal cell carcinoma in a population from Criciúma, Santa Catarina, Brazil Perfil clínico e histopatológico do carcinoma basocelular em amostra populacional de Criciúma, SC, Brasil - Letícia Pangendler Peres; Joana Zulian Fiorentin; Tamise da Silva Baptista; Deborah Grisolia Fuzina; Luiz Felipe de Oliveira Blanco (Sociedade Brasileira de Dermatologia, 2012)
Basal cell carcinoma is a local, invasive epidermal neoplasia, the most common type of which is nodular basal cell carcinoma. The objective of the present study was to evaluate the occurrence of basal cell carcinoma, characterizing its distribution in accordance with patients' age, gender, the site of the lesion and its histopathological characteristics. Anatomopathology reports of cases of basal cell carcinoma diagnosed in Criciúma, Santa Catarina, Brazil between June 2005 and June 2007 were analyzed. A descriptive, observational, cross-sectional study was conducted. The majority of patients were females over 40 years of age. Most of the tumors were of the nodular type and were situated on the face. There was ulceration in 27.5%, infiltration in 24.5% and invasion of the deep dermis in 61.8%. Local data must be evaluated in order to emphasize the importance of early diagnosis. O carcinoma basocelular é uma neoplasia epidérmica invasiva local, cujo tipo mais frequente é nódulo-ulcerativo. O objetivo foi estudar a ocorrência de CBC, caracterizando sua distribuição segundo idade, sexo, localização e características histopatológicas. Analisaram-se laudos anatomopatológicos de CBC, diagnosticados em Criciúma/SC, entre junho de 2005 e junho de 2007. Elaborou-se um estudo descritivo, observacional e transversal. Predominou após os 40 anos, no sexo feminino, do tipo nodular e localizado na face. Houve ulceração em 27,5%, infiltração em 24,5%, invasão de derme profunda em 61,8%, entre outros. É necessário conhecer dados locais para reforçar a importância do diagnóstico precoce.